Charter remedies in criminal cases - Asma, Matthew (Emond Montgomery Publications Limited, 2023)
"This book will be the second edition of our essential guide to when and how Charter remedies are available in criminal law. The book begins with "threshold matters," pertaining to when and how Charter remedies are available (e.g., which court, the standard of proof, procedural rules). The rest of the chapters focus on Charter remedies for particular outcomes in cases, ranging from excluding evidence, achieving a stay of proceedings, getting a sentence reduction, getting costs against the crown, making an application for habeas corpus review (unlawful detention), and legislative invalidity."– Provided by publisher.